Hospitalized Women's Willingness to Pay for Inpatient Screening Colonoscopy - Opeoluwa Olayinka; Jerome Gnanaraj; Waseem Khaliq (Mary Ann Liebert, 2022)
Background: Despite the proven mortality benefit of screening colonoscopy, ?27% of hospitalized women are nonadherent with colorectal cancer (CRC) screening guidelines. Colonoscopy is the most frequently used test for CRC screening in the United States. Although CRC is the second most common cause of cancer death in the United States, CRC screening has not been part of usual hospital care. Objective: This study explores how hospitalized women perceive value of inpatient screening colonoscopy by evaluating the mean amount of money that hospitalized women are willing to contribute toward the cost of a screening colonoscopy during a hospital stay. Methods: A cross-sectional bedside survey consisting of a contingent valuation questionnaire was used to assess the contribution these women considered to be justified for the convenience of an inpatient screening colonoscopy. The probit regression model was used for the analysis of contingent valuation data to predict mean willingness to pay toward inpatient screening colonoscopy. Results: Of the 312 enrolled patients, 48% were willing to pay a mean of $171.56 (95% confidence interval [CI] $37.59?$305.54, p?=?0.012) in advance toward the cost of an inpatient screening colonoscopy. After adjustment of possible sociodemographic and clinical covariates that could impact willingness to contribute, hospitalized women were willing to pay a mean of $178.41 (95% CI $40.67?$316.16, p?=?0.011). Conclusions: The findings of this study suggest that hospitalized women value the prospect of screening colonoscopy during hospitalization. Offering screening colonoscopy to nonadherent hospitalized women, especially those who are at high risk for developing CRC, may improve adherence among hospitalized women. This study is registered at www.clinicaltrials.gov (NCT04162925).